The Relationship between Metacognitive Reading Strategy Awareness and Reading Comprehension among freshman EFL Students, Ethiopia - Wudneh, Asalefew Mekuria (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
The study was an attempt to investigate the level of awareness on Metacognitive reading strategies among first year Ethiopian EFL students. It also tried to figure out the possible relationship between Metacognitive reading strategies use and reading comprehension achievement. Ninety-four EFL learners participated in the study. Metacognitive reading strategy inventory and reading comprehension test were used to collect the data. The data were analyzed through descriptive statistics to determine the mean value of strategies employed by the learners. Moreover, Pearson correlation coefficient was used to discover the association between reading strategy use and reading comprehension achievement. According to the findings Ethiopian EFL learners ,were almost near to the lower limit (M=2.55,Sd.=0.34)line of medium level reading strategy users. Furthermore, the use of metacognitive reading strategy had weak correlation (r=0.21,p=0.039) with reading comprehension achievement. The possible cause of this could be lack of awareness on how to regulate and monitor reading comprehension.